Frequency of dental caries in children in the Early Iron Age and the Medieval populations from Ukraine - Yanko, Nataliia Valentinovna; Artemyev, Andrij Vladislavovich; Kaskova, Lyudmyla Fedorivna (Anthropological Review, 2017)
In this paper we determine the caries frequency in children of the Early Iron Age (EIA) (the 9th – the 3d centuries BC) and the Medieval populations (the 8th – the beginning of the 15th century AD) from the Ukraine area, and compare the results with the data from several European populations who lived at the same time. The EIA is presented by 41 children skeletons, three of which were Cimmerian (the 9th – the 7th centuries BC) from the territory of contemporary Poltava region; 38 skulls from the territory of contemporary Poltava region and Crimea represented Scythian period (the 7th – the 3d centuries BC). Remains of 24 children from the Medieval populations were also examined, three of which were the ancient Hungarians from the Poltava region (the 8th – the 9th centuries AD), 6 Khazars from the Kharkiv region (the 8th – the 9th centuries), 1 child related the Old Rus culture from the Kyiv region (the 9th century), and 14 representatives of the nomadic populations in the Golden Horde period (the 13th – the beginning of the 15th century) from the Poltava and Zaporizhzhya regions. Taking in consideration the letter archaeobotanical studies we suggest that there were no major changes in the plants exploited during all the studied periods. The frequency of carious lesions in children from the Medieval populations (8.3% in individuals, 0.5% in deciduous teeth, and 0.4% in permanent teeth) is only slightly higher than those from the EIA period (2.4% in individuals and 0.2% in deciduous teeth). These indexes were not larger those of majority of European populations dated to the same historic period. Further isotopic, chemical and palaeobotanical studies of the additional sites, with sufficient sample sizes, allow us to learn so much more of the cariogenic factors in children of the past populations from the Ukraine area.